Analisis Latar Belakang Keluarga Siswa Bermasalah : (Studi Kasus: SMP Swasta Rokita Sari Bangun) - Amini Amini (Cendikia : Media Jurnal Ilmiah Pendidikan, 2021)
Every child has characteristics and traits or innate characteristics (heredity) and characteristics obtained from environmental influences. Innate characteristics are hereditary characteristics that are owned since birth, both concerning biological factors and social psychological factors. Problematic children are children whose behavior does not follow school rules and regulations, these students tend to be inactive and unproductive at school, and ultimately have an impact on students' graduation. the problem. The above phenomenon is a motivation for the author in conducting research at Rokita Sari Bangun Purba Private Junior High School. Based on the results of the study, several conclusions were drawn as follows: a). The higher the level of family income, the less likely the child has problems in school from that family. b). The smaller the number of family members, the less likely the child will have problems at school. c). The more likely the child is in trouble at school if the father is not involved in the education and training of the child. If both parents are involved in the development and guidance of children's education, the less likely the child has problems. d). The type of work that parents do, such as mocok-mocok, has the greatest chance of having problems with their children at Rokita Sari Bangun Purba Private Junior High School.